Measures for Resource Saving for Diesel Locomotives - Aulin, Dmytro; Zinkivskyi, Artem; Anatskyi, Oleksandr; Kovalenko, Dmytro (International Journal of Engineering and Technology, 2018)
This article discusses the measures for efficient use of fuel and energy resources in the railway industry. The calculation of the initial moment of starting the diesel engine and the necessary position of its crankshaft is made, on the basis of which it is proposed to modernize the locomotive start-up system with a decompressor. These measures are aimed at reducing the dynamic loads of engine components and reducing their wear and tear, as well as failure preventing. A method for the clean-up of fuel systems and the cylinder-piston diesel engine group of diesel locomotives was developed and tested using a special cleaning liquid that dissolves and removes solidified particles from pipelines and tanks. Measures have been proposed on the use of advanced models to test the modernized locomotives that will reduce the duration of the tests, resource and economic costs. The use of advanced testing model involves choosing the level of accuracy of the test results and, consequently, their duration and cost.
Keywords: Carbon Deposit; Clean-in-place; Diesel Engine; Resource Saving; Starting Aid; Testing Model.